Novel gas hold-up probe and application in flotation - F. J. Tavera; J. A. Finch (The Institute of Materials, Minerals and Mining, 1905)
A probe suitable for on-line measurements of gas hold-up in industrial flotation systems has been developed. It is based on an open cell for measurement of slurry-gas conductivity and a novel syphon cell for measurement of slurry-only conductivity. The desired behaviour of the two cells was demonstrated and estimates of gas hold-up were shown to be in good agreement with independent measurements. The gas hold-up probe was used as a diagnostic tool to assess the operation of flotation columns. Differences in gas hold-up between baffled sections in two industrial columns were detected